Prognostic significance of NT-proBNP and sST2 in patients with heart failure with preserved and mildly reduced ejection fraction - V. I. Podzolkov; N. A. Dragomiretskaya; A. V. Tolmacheva; I. I. Shvedov; A. A. Ivannikov; I. V. Akyol (Столичная издательская компания, 2023)
Aim. To study the prognostic significance of cardiobiomarkers - NT-proBNP and soluble suppression of tumorigenecity (sST2) in patients with CHF with preserved (CHFpEF) and mildly reduced EF (CHFmrEF).Material and methods. Along with a clinical examination, 207 patients (111 men and 96 women), mean age - 72.6 ± 11.4 years, underwent tests for the level of NT-proBNP and sST2 in serum. All patients were divided into 3 groups: 1 - CHFpEF (n=85), 2 - CHFmrEF (n=50); 3 (comparison group)- CHFrEF (n=72). All patients signed informed consent to participate in the study. The primary endpoint was all-cause death in 12 months. Statistical processing of the results was carried out using the Statistica 12.0 and Medcalc programs.Results. The initial values ​of NT-proBNP in patients with CHFmrEF were 691.9 [248; 1915.5] pg/ml and were significantly higher than those of CHFpEF - 445.8 [214.6; 945.7] pg/ml, but significantly lower than in CHFrEF - 1131.4 [411.5;3039.5] pg/ml, p<0.05. sST2 values ​​in group 1 (23.21 [12.17;48.7] ng/ml and group 2 (27.11 [16.98;53.76] ng/ml) did not differ, but were significantly lower than in patients with CHFrEF (44.6 [21.1; 93.5] ng/ml). After a median of 12 months 51 patients reached the primary endpoint.  All-causes mortality in patients with HFpEF was 11.8%, HFmrEF - 31.9% (p <0.05), and HFrEF - 36%. A retrospective analysis of the data showed that in patients independent of their initial ejection fraction, who survived for 12 months, the levels of NT-proBNP and sST2 were significantly lower than those of the deceased.  In survivors and deceased patients with CHFpEF the values ​​of NT-proBNP and sST2 were 443 [154;862,8] vs 1143,2 [223,9;2021,9] pg/ml (p=0.009) and 22,8 [12,3;33,8]  vs 26,8 [9,6;74,8] ng/mL (p<0.05). In survivors and deceased patients with CHFmrEF the values ​​of NT-proBNP and sST2 were 397.4 [128.9;1088.5] vs 1939.7 [441.9;2536] pg/ml (p=0.009) and 18.6 [14.9;30.27.1] vs 59.9 [53.76;84.4] ng/mL (p=0.002). There were no significant differences in NT-proBNP and sST2 values ​​in patients with cardiac and non-cardiac causes of death. sST2 parameters in deceased patients with CHFpEF (26.8 [9.6;74.8] ng/mL) and CHFmrEF (59.9 [53.76;84.4] ng/mL) also had no significant differences (p >0.05). At ROC analysis to one-year adverse events, both NT-proBNP and sST2 showed a significant predictive value in patients with EF >40% with an optimal cut-off value of 746 pg/ml (AUC 0.709; p = 0.005, sensitivity 62%, specificity 69%) and 27.1 ng/ml (AUC 0.742; p = 0.03, sensitivity 80%, specificity 75.8%) respectively.Conclusion: NT-proBNP levels >746 pg/ml and sST2 >27.1 ng/ml should be considered as predictors of poor prognosis in CHF patients with LVEF >40%.